Critical Roles of Mechanical Properties of Solid Electrolyte Interphase for Potassium Metal Anodes - Gao, Yao; Hou, Zhen; Zhou, Rui; Wang, Danni; Guo, Xuyun; Zhu, Ye; Zhang, Biao (Advanced functional materials, 2022)
The mechanical properties of the solid electrolyte interphase (SEI) have attracted increasing attention, but their importance in guiding electrolyte design remains ambiguous. Here it is revealed that, despite a decrease in ionic conductivity for both electrolyte and SEI, exceptional cycling performance of K‐metal batteries is achieved in a low concentration carbonate electrolyte by optimizing the mechanical stability of the SEI. The SEI formed in the studied carbonate electrolytes is predominantly organic. Its inorganic content increases with increasing electrolyte concentration and corresponds to an increase in Young's modulus (E) and ionic conductivity of SEI and a decrease in elastic strain limit (εY). The maximum elastic deformation energy combines effects of E and εY, achieving a maximum in 0.5 m electrolyte. Finite element simulations indicate that SEI with low either E or εY inevitably triggers dendrite growth. These findings foreshadow an increased focus on the mechanical properties of the SEI, where low concentrations of carbonate electrolytes display merit. The mechanical stability of the solid electrolyte interphase (SEI) is found to outweigh ionic conductivity in determining the performance of potassium metal anodes in carbonate electrolytes. The organic‐dominated composite structure of SEI causes its ionic conductivity and Young's modulus (E) to increase with increasing electrolyte concentration, but elastic strain limit (εY) to decrease. Low E or εY of the SEI activates dendrite growth due to the inhomogeneous electric field.